2013
DOI: 10.1097/acm.0b013e318294fc7b
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Misuse of Prescription Stimulants as “Cognitive Enhancers” by Students at One Academic Health Sciences Center

Abstract: Prescription stimulant misuse was prevalent among participating students, but further research is needed to describe prevalence among future health care workers more generally. The implications and consequences of such misuse require further study across professions with emphasis on investigating issues of academic dishonesty (e.g., "cognitive enhancement"), educational quality, and patient safety or health care quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 7 publications
2
49
1
Order By: Relevance
“…Moderate lifetime prevalence estimates of stimulant misuse have also been reported among undergraduate and graduate health care students (11%), dental and dental hygiene students (12.4%), and general samples including both undergraduate and graduate students (16.2%–17.5%) 50,108110…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate lifetime prevalence estimates of stimulant misuse have also been reported among undergraduate and graduate health care students (11%), dental and dental hygiene students (12.4%), and general samples including both undergraduate and graduate students (16.2%–17.5%) 50,108110…”
Section: Resultsmentioning
confidence: 99%
“…Finally, all types of students (adolescents, adults, and medical) performing worse academically appear to be more likely to engage in nonmedical prescription stimulant use 56,99,101,105. Indeed, this review found that the most commonly reported reasons university students take prescription stimulants are related to academics, and studies suggest that during periods of high academic stress, college students may be more likely to use prescription stimulants, as indicated by self-report measures and by measurements of stimulant levels in campus wastewater samples 49,54,56,105,108,110,113,115…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high rates of prescription stimulant misuse among young adults without ADHD who report cognitive and/or academic enhancement as the primary reason for misusing stimulant medication (Advokat, Guidry & Martino, 2008; Bossaer et al, 2013; DeSantis, Webb & Noar, 2008; Garnier-Dykstra et al, 2012; Habibzadeh et al, 2011; Novak, Kroutil, Williams, & Van Brunt, 2007; Rabiner et al, 2009; Teter, McCabe, Cranford, Boyd, & Guthrie, 2005; White et al, 2006; Weyandt et al, 2009), the obvious empirical question is whether prescription stimulants truly enhance the cognitive and/or academic functioning of these individuals or whether they simply believe that they do. This is an especially intriguing question given that grade point average (GPA) has been found to be negatively correlated with stimulant misuse among college students (Benson et al, 2015; Weyandt et al, 2013).…”
Section: Are Prescription Stimulants Truly Neurocognitive Enhancers?mentioning
confidence: 99%
“…Students of a highly competitive UK university deemed the competitive advantage PCE can give as one of the most important concerns regarding its use: an advantage due to PCE use was found most morally wrong when no other competitors were taking the substance, relating competitive to distributive fairness and peer pressure (Scheske and Schnall, 2012). Moreover, an online survey by Bossaer et al (2013) demonstrated that 60% of the 372 student respondents agreed that PCE provides users with an unfair advantage over other students. An almost identical amount of just over half of the respondents (56%) believed that PCE use for study purposes could be seen as academic dishonesty.…”
Section: Fairnessmentioning
confidence: 99%